Theoretical Issues on Crime Prevention - Hai, Nguyen Khac (VNU Journal of Science: Legal Studies, 2024)
Crime is a complex, diverse and constantly changing phenomenon. Crime prevention strategies, programs and measures selected for a nation or community should be compatible with the limited resources of that society to ensure effectiveness. Therefore, awareness and prediction of crime phenomenon, the identification of the desired prevention effect, and the expansion of prevention initiatives both in the public and private sectors to control it are essential. In addition, this study opens up new avenues for research in Vietnam and offers a variety of approaches to categorize and systematize crime preventive actors and institutions. The article also analyzes the basic principle underlying the guidelines for crime prevention. Based on the theoretical issues that have been resolved, the article suggests further research directions in Vietnam.